Relating social learning spaces to student's involvement in universities in Davao City - Delute, Cyla C. (2021)
Aside from learning inside the classroom with the instructors, academicsocial interaction plays an important role in the overall experience andlearning of a student inside their campus community. This study wanted todescribe how students use of Social Learning Spaces to socially interactrelates to their involvement in the campus and to also know the factors thatcontributes to how students use the social learning spaces. To gather theneeded data for this study, the researcher used photo elicitation and surveyquestionnaires and also interviewed the respondents.The results of the study suggests that students in universities in DavaoCity get more involved in their university by interacting and working with peersoutside class hours and studying independently inside their campus. Most ofthe university students get involved by using the social learning spaces asspace for individual and collaborative learning. An average of 3-5 hours aweek and 1-3 times a month the student spends their time interacting withtheir peers inside the campus. When students were asked on what sociallearning spaces, they need the most, majority of the students said that theyneed spaces equipped with tables and chairs. Research results shows thatthermal comfort, furniture configuration, work surface, natural lighting, andaccess to electrical outlets are spatial characteristics students were most concerned of. Social Learning Spaces encourages students to participate toacademic interaction in a way that if the social spaces were provided and thespatial characteristics the students needed were met, they are more encouraged to involve themselves to university activities and other academic-related activities.